Conspicuity of prostate cancer on multiparametric magnetic resonance imaging: A cross‐disciplinary translational hypothesis. Issue 11 (13th September 2020) - Norris, Joseph M.; Simpson, Benjamin S.; Freeman, Alex; Kirkham, Alex; Whitaker, Hayley C.; Emberton, Mark
Abstract: Pre‐biopsy multiparametric magnetic resonance imaging (mpMRI) has transformed the risk stratification and diagnostic approach for suspected prostate cancer. The majority of clinically significant prostate cancers are visible on pre‐biopsy mpMRI, however, there are a subset of significant tumors that are not detected by mpMRI. The radiobiological mechanisms underpinning mpMRI‐visibility and invisibility of these cancers remain uncertain. Emerging evidence suggests that mpMRI‐visible tumors are enriched with molecular features associated with increased disease aggressivity and poor clinical prognosis, which is supported by short‐term endpoints, such as biochemical recurrence following surgery. Furthermore, at the histopathological level, mpMRI‐visible tumors appear to exhibit increased architectural and vascular density compared to mpMRI‐invisible disease. It seems probable that the genomic, pathological, radiological, and clinical features of mpMRI‐visible and mpMRI‐invisible prostate cancers are interrelated. Here, we propose a novel cross‐disciplinary theory that links genomic and molecular evidence with cellular and histopathological appearances, elucidating both the mpMRI visibility and clinical status of significant prostate cancer.